The Role of Fiscal Decentralization in Enhancing Regional Financial Independence in Indonesia - Tuti Dharmawati; Wa Ode Muhardiana; Wa Ode Aprisilia Z.A (PT. Banjarese Pacific Indonesia, 2024)
This study aims to analyze the role of fiscal decentralization in enhancing regional financial independence in Indonesia. Using a qualitative approach and literature review methodology, the research examines the role of fiscal decentralization in promoting regional financial autonomy in Indonesia. The analysis compares the effectiveness of fiscal decentralization policies in fostering financial independence across various regions in the country. Fiscal decentralization has demonstrated positive impacts by granting regions greater freedom to determine development priorities and explore funding sources. Regions with strong economic potential and natural resources can increase their locally generated revenue (Pendapatan Asli Daerah or PAD) to support development. However, this policy also creates disparities among regions, where wealthier regions manage their finances independently while poorer regions remain reliant on central government transfers. Moreover, limited managerial capacity in some regions hampers the policy's effectiveness. Fiscal decentralization can strengthen regional financial independence if accompanied by enhanced financial management capacity and fiscal policy adjustments.